Implementation Evaluation Tax Holiday and Tax Allowance Policies on the Growth of Foreign Investment - Dahliah Dahliah; Julianty Sidik Tjan; Fauziah Dwi Aulia (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study investigates the impact of tax holidays and tax allowance policies on the development of foreign investment in the BKPMD South Sulawesi Province from 2017 to 2020. Documentation is used for data collection techniques that involve direct observation of the object of study. Descriptive statistical analysis, classical assumption tests (normalizes test, heteroskedasticity test, multicollinearity test), and testing of the entire hypothesis via partial testing, simultaneous testing, and determination coefficient test are employed for data analysis. This study demonstrates that applying tax holidays and tax allowances do not affect the growth of a foreign investment. Therefore, the government should streamline licensing and conditions and promote policy facilities, so investors are fully aware of them. This is because factors other than tax incentives determine investment, such as the size of the domestic market, wage levels and worker productivity, infrastructure availability, government spending growth, inflation rates, interest rates, and investment risks. Tax exemptions and tax credits are still inadequate for enthusiasts. This demonstrates that the tax holiday and tax credit cannot be considered effective and efficient regarding investor interests. We recommend that the government or relevant agencies immediately improve and review the licensing process at the central and regional levels so as not to diminish investor confidence in Indonesia's legal certainty; improving the investment climate through better regulations can positively impact the investment climate. The investment tax incentive policy must be widely publicized and promoted so that investors can be aware of it and benefit from it.